AIRPORT INFRASTRUSTURE AS AN INTEGRATIVE BUSINESS FORMATION - Vsevolod Yu. Tiakht (Статистика и экономика, 2016)
The article considers the airport as amultifunctional formation of infrastructure, designed to provide many types of services to both individuals and legal entities.For the successful implementation ofbusiness activities related to the provision of airport services, requires speciﬁc resources, including human resources,and the established mechanism interaction between internal infrastructure units. In order to be able to detailed analysis ofthe phenomenon of airport infrastructureare highlighted its levels depending on thesubject of airport services.